Sodium bentonite spherical cat litter and preparation method thereof

By preparing sodium -shaped cat litter with natural soap ore, sodium dither and viscous substances, solve the problem of low water absorption, unstable and high dust content of the existing cat litter, and the high content of the existing cat litter. High -performance, environmentally friendly cat sand products.

CN119344224APending Publication Date: 2025-01-24INNER MONGOLIA R&L BENTONITE TECH CO LTD

Patent Information

Application Number
CN202411663094.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing cat litter with natural clay as the main raw material has problems such as high dust content, easy powdering, low water absorption, and unstable agglomeration. Cat litter with plant fibers and starch as the main raw material should not be processed into spherical particles. There are problems such as mildew, high cost, and limited raw material sources.

Method used

Adopt natural soap ore, sodium modifiers, and sodium -shaped cat litter -shaped cat litter with aquatic solution containing viscous substances. Sodium flour powder is obtained through steps of squeezing, stacking, drying, and grinding. The aquatic solution is mixed with grains, and spherical cat litter is obtained after drying and sieved.

Benefits of technology

It improves the water absorption rate, clumping strength and deodorizing effect of cat litter, reduces the amount of dust and pulverization rate, enhances the weather resistance and environmental friendliness of the product, and is suitable for raising pet cats.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of cat litter, and particularly relates to sodium bentonite spherical cat litter and a preparation method thereof. The sodium bentonite spherical cat litter is prepared from natural bentonite ore, a sodium modifier and an aqueous solution containing viscous substances. Compared with an existing spherical cat litter, the sodium bentonite spherical cat litter is better in water absorption, lower in dust capacity, higher in adsorption capacity, almost free of inhalable particles in the using process, higher in deodorization and odor removal capacity, better in water absorption, caking strength and deodorization effect and capable of being used for a long time. The spherical cat litter does not mildew in the processing, storage, transportation and use processes, does not generate toxin or unfriendly odor, is higher in weather resistance, is very low in content of heavy metals such as lead and arsenic, is environment-friendly in the preparation and use processes, and is better and more excellent in comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cat litters, and particularly relates to sodium bentonite spherical cat litter and a preparation method thereof. Background Art

[0002] Cat litter is an essential consumable for pet cats, and its consumption is huge. Against the background of rapid growth in consumption year by year, cat litter products have shown the characteristics of diversified raw materials, diverse varieties, and complex functions.

[0003] For example, patent applications CN110100746A, CN110100746A, CN104489424A, CN108849559A, CN113100086A, and CN103348924A respectively disclose cat litters with natural bentonite, sodium bentonite, modified bentonite, attapulgite, zeolite, and bentonite / zeolite composite as main raw materials and preparation methods thereof; patent applications CN117530188A and CN116235786A disclose cat litters with plant fiber and starch as main raw materials and preparation methods thereof. Patent applications CN110050707A, CN109089905B, and CN107711533B disclose cat litters with deodorizing, antibacterial and other functions and preparation processes thereof.

[0004] In general, cat litter made from natural clay has significant advantages such as relatively abundant resources, strong technical adaptability, relatively low cost, diverse product forms, products that will not mold, environmentally friendly properties, and high market recognition.

[0005] However, cat litter with natural clay as the main raw material has shortcomings such as high dust content, easy pulverization, low water absorption, and unstable clumping. At the same time, cat litter with plant fiber and starch as the main raw materials is not suitable for processing into spherical particles, and there are problems such as easy mildew of the product, high cost, and limited source of raw materials. Summary of the invention

[0006] Based on the above technical background, the main purpose of the present invention is to provide a sodium bentonite spherical cat litter and a preparation method thereof to overcome the deficiencies in the prior art.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The first aspect of the present invention is to provide a sodium-containing bentonite spherical cat litter, wherein the sodium-containing bentonite spherical cat litter is prepared from natural bentonite ore, a sodium-containing modifier and an aqueous solution containing a viscous substance; The mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100:(3-8):(21-28).

[0008] Preferably, the mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100:7:26.

[0009] Preferably, the sodium modification agent is selected from one or more of sodium bicarbonate, sodium carbonate and sodium hydroxide.

[0010] Preferably, the mass concentration of the viscous substance in the aqueous solution containing the viscous substance is 0.3% to 9%.

[0011] Preferably, the viscous substance is selected from one or more of polyacrylamide, carrageenan and methylcellulose.

[0012] Preferably, the moisture content of the sodium bentonite spherical cat litter is 6.5%-9.5%, and the bulk density is 0.78-1.02 g / cm 3 , deodorization effect ≤19.5ppm, calculated as NH3, formaldehyde not detected, lead ≤30.0mg / kg, arsenic ≤12.0mg / kg; The application indexes of the sodium bentonite spherical cat litter are: water absorption rate ≥42%, pulverization rate ≤0.9%, and clumping strength ≥11 times.

[0013] The second aspect of the present invention is to provide a method for preparing the sodium bentonite spherical cat litter according to the first aspect of the present invention, the method comprising the following steps: Step 1, mixing natural bentonite ore and a sodium modifier evenly, and then extruding, stacking, drying, and grinding to obtain sodium bentonite powder; Step 2: Mix the sodium bentonite powder and the aqueous solution containing the sticky substance to form granules, sieve to obtain wet sodium bentonite spherical particles, and then dry and sieve to obtain sodium bentonite spherical cat litter.

[0014] In step 1, Preferably, the stacking is carried out at room temperature for 40 to 50 hours.

[0015] Preferably, the drying is carried out at 100 to 120° C. for 20 to 45 minutes; Preferably, the powder ground to a fineness of 200 mesh or less accounts for more than 92%.

[0016] In step 2, Preferably, sieving to obtain wet sodium bentonite spherical particles of 1 to 4 mm; Preferably, after sieving, the wet sodium bentonite spherical particles are dried at 220-290° C. for 20-45 min; Preferably, after drying, fine particles with a particle size of less than 1 mm are removed by sieving, and finally sodium bentonite spherical cat litter with a particle size of 1 to 4 mm is obtained.

[0017] The beneficial effects of the present invention are: (1) The sodium-modified bentonite spherical cat litter of the present invention is mainly made of natural bentonite ore, which comes from nature. The sodium-modified bentonite ore is modified by adding a sodium-modified modifier to obtain sodium-modified bentonite powder. Compared with bentonite, attapulgite clay and non-sodium-modified bentonite, the spherical cat litter prepared from the sodium-modified bentonite powder of the present invention has better water absorption, lower dust content, stronger adsorption capacity, and almost no inhalable particulate matter is generated during use, and the deodorizing and odor removal ability is stronger.

[0018] The sodium bentonite powder of the present invention has good binding properties with water or organic solvents, and has excellent effects such as high expansion, thixotropy, suspension, dispersibility, thickening, stability and adsorption, and is very suitable for preparing high-performance spherical cat litter. The present invention prepares cat litter by combining sodium bentonite powder with an aqueous solution containing a viscous substance to granulate, which can improve the water absorption rate, agglomeration strength and deodorization effect of the prepared cat litter, and the comprehensive performance is better and more excellent.

[0019] Compared with organic raw materials such as beans and corn starch, the sodium bentonite powder of the present invention is unlikely to cause mildew, produce toxins, or generate unfriendly odors during processing, storage, transportation and use, and has stronger weather resistance.

[0020] In addition, the sodium bentonite powder and spherical cat litter of the present invention contain very low content of heavy metals such as lead and arsenic, and the preparation and use processes are environmentally friendly.

[0021] (2) The sodium processing technology and preparation method of the present invention are simple, suitable for the preparation of high-performance sodium-treated spherical cat litter, can significantly improve the use efficiency of spherical cat litter, can realize large-scale industrial production, fill the gap in the preparation of sodium-treated spherical cat litter from natural bentonite, and such modified sodium-treated bentonite powder can be used to prepare spherical cat litter with excellent performance.

[0022] (3) The sodium bentonite spherical cat litter of the present invention can be suitable for the breeding of urinating pets, especially for the breeding of pet cats. DETAILED DESCRIPTION

[0023] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.

[0024] The first aspect of the present invention is to provide a sodium-containing bentonite spherical cat litter, which is prepared from natural bentonite ore, a sodium-containing modifier and an aqueous solution containing a viscous substance.

[0025] The natural bentonite ore refers to naturally formed rather than artificially synthesized bentonite powder or aggregate.

[0026] In view of the problems existing in natural clay cat litters represented by bentonite, such as high dust content, easy pulverization, low water absorption, unstable agglomeration, and their influencing mechanisms, the inventors found that although clay minerals such as montmorillonite have a layered structure and abundant surface charge, their dioctahedrons are mainly composed of trivalent aluminum ions, and the cations in the interlayer domain are mostly monovalent cations. Its water adsorption capacity is not in the optimal state, that is, the water absorption rate is not optimal. This is the main reason why cat litters prepared from this type of raw materials have low water absorption and poor agglomeration; in addition, clay minerals such as montmorillonite have abundant surface unsaturated charges, which are not effectively neutralized in spherical cat litters, which is the main reason why this type of product has high dust content and is easy to pulverize.

[0027] In view of this, after further research, the inventors further discovered that when natural clay cat litter uses natural bentonite and its sodium-based product sodium bentonite with similar properties to bentonite, especially when sodium-based saponite is the main functional component of the bentonite, its trioctahedron is mainly composed of divalent magnesium ions, and the divalent cations in the interlayer domain are partially replaced by monovalent sodium cations. Its water adsorption capacity is in a more optimal state, that is, the water absorption rate can reach the maximum, which can increase the water absorption rate of the cat litter and improve its clumping performance.

[0028] The mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100:(3-8):(21-28).

[0029] Preferably, the mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100:7:26.

[0030] The sodium modification agent is selected from one or more of sodium bicarbonate, sodium carbonate and sodium hydroxide. Preferably, the sodium modification agent is sodium bicarbonate.

[0031] The invention can further improve the water absorption rate and agglomeration strength of the cat litter by adding sodium modification.

[0032] The mass concentration of the viscous substance in the aqueous solution containing the viscous substance is 0.3% to 9%. Preferably, the mass concentration of the viscous substance in the aqueous solution containing the viscous substance is 6.5%.

[0033] The viscous substance is selected from one or more of polyacrylamide, carrageenan and methyl cellulose. Preferably, the viscous substance is methyl cellulose.

[0034] The moisture content (%) of the sodium bentonite spherical cat litter is 6.5%-9.5%, and the bulk density (g / cm 3): 0.78-1.02, deodorization effect (ppm, calculated as NH3) ≤ 19.5, formaldehyde not detected, lead (mg / kg) ≤ 30.0, arsenic ≤ 12.0. The application indicators of the sodium bentonite spherical cat litter are: water absorption rate (%) ≥ 42, powdering rate (%) ≤ 0.9, and agglomeration strength (times, 30cm drop without breaking times) ≥ 11.

[0035] Preferably, the moisture content (%) of the sodium bentonite spherical cat litter is 7.4%, and the bulk density (g / cm 3 ): 0.82, deodorization effect (ppm, as NH3): 12.0, formaldehyde not detected, lead (mg / kg): 12.0, arsenic: 1.5; water absorption rate (%): 45, powdering rate (%): 0.5, clumping strength (times, 30cm drop without breaking times): 15.

[0036] The second aspect of the present invention is to provide a method for preparing the sodium bentonite spherical cat litter according to the first aspect of the present invention, the method comprising the following steps: Step 1, mixing natural bentonite ore and a sodium modifier evenly, and then extruding, stacking, drying, and grinding to obtain sodium bentonite powder; Step 2: Mix the sodium bentonite powder and the aqueous solution containing the sticky substance to form granules, sieve to obtain wet sodium bentonite spherical particles, and then dry and sieve to obtain sodium bentonite spherical cat litter.

[0037] The above steps are described in detail below.

[0038] In step 1, the stacking is carried out at room temperature for 40 to 50 hours, preferably for 48 hours.

[0039] The drying is performed at 100-120° C. for 20-45 min. Preferably, the drying is performed at 110° C. for 30 min.

[0040] The powders ground to a fineness of 200 mesh and below account for more than 92%.

[0041] The chemical composition of the sodium bentonite powder is: SiO2 49.20%-52.88%, Al2O3 14.58%-16.65%, TiO2 0.32%-0.38%, ( , which is the sum of FeO and Fe2O3 without distinguishing the iron valence state, the same below) 3.45%-5.54%, MgO 4.16%-4.88%, CaO 1.08%-2.35%, K2O 0.08%-0.11%, Na2O 1.10%-4.91%, and the ignition loss is 17.23%-20.74%. The substances lost by ignition include but are not limited to adsorbed water, structural water, CO2 and SO2.

[0042] Preferably, the chemical composition of sodium bentonite powder is: SiO2 49.72%, Al2O3 14.88%, TiO2 0.36%, 4.92%, MgO 4.29%, CaO 2.21%, K2O 0.09%, Na2O 3.88%, and the loss on ignition is 19.31%.

[0043] The mineral composition of sodium bentonite powder is: 92%-95% of saponite, 3%-5% of montmorillonite, and 2%-4% of quartz. The montmorillonite is a general term that does not distinguish between sodium-based montmorillonite and calcium-based montmorillonite; the quartz is α-quartz in mineralogy.

[0044] Preferably, the mineral composition of the sodium bentonite powder is: 93% saponite, 3.5% montmorillonite, and 3.5% quartz.

[0045] In step 2, sieving is performed to obtain 1-4 mm wet sodium bentonite spherical particles.

[0046] After sieving, the wet sodium bentonite spherical particles are dried at 220-290° C. for 20-45 min.

[0047] Preferably, after sieving, the wet sodium bentonite spherical particles are dried at 270° C. for 25 min.

[0048] After drying, fine particles with a particle size of less than 1 mm are removed by sieving, and finally sodium bentonite spherical cat litter with a particle size of 1 to 4 mm is obtained.

[0049] Example The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.

[0050] Example 1 Weigh 100 kg of natural bentonite ore and 7 kg of sodium carbonate, mix the two evenly, then extrude and pile them at room temperature for 48 hours (the materials are placed in a sunshade with ventilation on all sides), then dry them at 110°C for 30 minutes, and then grind the ore powder until the powder with a fineness of 200 mesh or less accounts for more than 92%, thereby obtaining sodium bentonite powder.

[0051] The sodium bentonite powder was granulated on a granulation disk with 260 kg of an aqueous solution containing 6.5% methylcellulose by mass, and sieved to obtain wet sodium bentonite spherical particles of 1 to 4 mm.

[0052] The wet sodium-treated spherical bentonite particles are dried at 270° C. for 25 minutes, and fine particles with a particle size of less than 1 mm are removed by sieving, so as to finally obtain sodium-treated bentonite spherical cat litter with a particle size of 1 to 4 mm.

[0053] The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 48.22%, Al2O3 14.43%, TiO2 0.35%, ( , which is the sum of FeO and Fe2O3 without distinguishing the iron valence state, the same below) 4.77%, MgO 4.16%, CaO 2.14%, K2O 0.09%, Na2O 10.52%, and the loss on ignition is 14.99%.

[0054] The sodium bentonite powder was tested by X-ray powder diffraction internal standard method, and the mineral composition of the sodium bentonite powder was measured to be: saponite 93%, montmorillonite 3.5%, and quartz 3.5%.

[0055] The sodium bentonite powder was sieved through a standard sieve for fineness test, and it was found that the powder with a fineness of 200 mesh and below accounted for 93.0%.

[0056] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.4%; bulk density (g / cm 3 ): 0.82; Deodorizing effect (ppm, as NH3): 12.0; Formaldehyde was not detected; Lead (mg / kg) content: 12.0, Arsenic: 1.5; Water absorption rate (%): 45: Powdering rate (%): 0.5, Agglomeration strength (times, 30cm drop without breaking times): 15.

[0057] Example 2 The preparation of sodium bentonite spherical cat litter was carried out in a similar manner to Example 1, except that the amount of sodium carbonate was increased to 8 kg. The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 49.25%, Al2O3 14.74%, TiO2 0.36%, 4.87%, MgO 4.25%, CaO 2.19%, K2O 0.08%, Na2O 4.40%, and the loss on ignition is 19.51%.

[0058] The sodium bentonite powder was tested by X-ray powder diffraction internal standard method, and the mineral composition of the sodium bentonite powder was measured to be: saponite 93%, montmorillonite 3.5%, and quartz 3.5%.

[0059] The sodium bentonite powder was sieved through a standard sieve for fineness test, and it was found that the powder with a fineness of 200 mesh and below accounted for 93%.

[0060] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 8.4%; bulk density (g / cm 3 ): 0.81; Deodorization effect (ppm, in terms of NH3): 13.0; Water absorption rate (%): 42; Powdering rate (%): 0.85; Agglomeration strength (times, 30cm drop without breaking): 13.

[0061] Example 3 The preparation of sodium bentonite spherical cat litter was carried out in a similar manner to Example 1, except that the amount of sodium carbonate was reduced to 3 kg. The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 52.35%, Al2O3 15.67%, TiO2 0.38%, 5.18%, MgO 4.52%, CaO 2.33%, K2O 0.09%, Na2O 1.70%, and the loss on ignition is 17.42%.

[0062] The sodium bentonite powder was tested by X-ray powder diffraction internal standard method, and the mineral composition of the sodium bentonite powder was measured to be: saponite 93%, montmorillonite 3.5%, and quartz 3.5%.

[0063] The sodium bentonite powder was sieved through a standard sieve for fineness test, and it was found that the powder with a fineness of 200 mesh and below accounted for 92.5%.

[0064] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.6%; bulk density (g / cm 3 ): 0.88; Deodorizing effect (ppm, as NH3): 12.5; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 43; Powdering rate (%): 0.8; Agglomeration strength (times, 30cm drop without breaking): 12.

[0065] Example 4 The preparation of sodium bentonite spherical cat litter was carried out in a similar manner to Example 1, except that sodium bicarbonate was used instead of sodium carbonate.

[0066] The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 49.73%, Al2O3 14.88%, TiO2 0.36%, 4.91%, MgO 4.29%, CaO 2.21%, K2O 0.08%, Na2O 4.91%, and the loss on ignition is 18.29%.

[0067] The sodium bentonite powder was tested by X-ray powder diffraction internal standard method, and the mineral composition of the sodium bentonite powder was measured to be: saponite 93%, montmorillonite 3.5%, and quartz 3.5%.

[0068] The sodium bentonite powder was sieved through a standard sieve for fineness test, and it was found that the powder with a fineness of 200 mesh and below accounted for 92.0%.

[0069] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.4%; bulk density (g / cm 3 ): 0.82; Deodorizing effect (ppm, as NH3): 12.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 45.4, Powdering rate (%): 0.6, Agglomeration strength (times, 30cm drop without breaking): 14.

[0070] Example 5 The preparation of sodium bentonite spherical cat litter was carried out in a similar manner to Example 1, except that sodium hydroxide was used instead of sodium carbonate.

[0071] The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 49.73%, Al2O3 14.88%, TiO2 0.36%, 4.91%, MgO 4.29%, CaO 2.21%, K2O 0.08%, Na2O 4.91%, and the loss on ignition is 18.29%.

[0072] The sodium bentonite powder was tested by X-ray powder diffraction internal standard method, and the mineral composition of the sodium bentonite powder was found to be the same as that in Example 1.

[0073] The sodium bentonite powder was sieved through a standard sieve for fineness test, and it was found that the powder with a fineness of 200 mesh and below accounted for 92.3%.

[0074] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.2%; bulk density (g / cm 3 ): 0.82; Deodorizing effect (ppm, as NH3): 11.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 43; Powdering rate (%): 0.6; Agglomeration strength (times, 30cm drop without breaking): 14.

[0075] Example 6 The preparation of sodium bentonite spherical cat litter was carried out in a similar manner to Example 1, except that the sodium bentonite powder was granulated on a granulation disk using an aqueous solution containing 0.3% methylcellulose.

[0076] The chemical composition, mineral composition and powder fineness of the modified bentonite powder were the same as those in Example 1.

[0077] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.6%; bulk density (g / cm 3 ): 0.83; Deodorizing effect (ppm, as NH3): 12.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 44, Powdering rate (%): 0.6, Agglomeration strength (times, 30cm drop without breaking): 13.

[0078] Example 7 The preparation of sodium bentonite spherical cat litter was carried out in a manner similar to that of Example 1, except that the sodium bentonite powder was granulated on a granulation disk using an aqueous solution containing 9.0% methylcellulose.

[0079] The chemical composition, mineral composition and powder fineness of the modified bentonite powder were the same as those in Example 1.

[0080] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.2%; bulk density (g / cm 3): 0.84, deodorizing effect (ppm, as NH3): 11.8; formaldehyde not detected; lead (mg / kg): 12.0, arsenic: 1.5; water absorption rate (%): 42; powdering rate (%): 0.4; clumping strength (times, 30cm drop without breaking): 11.

[0081] Example 8 The sodium-containing bentonite spherical cat litter was prepared in a manner similar to that of Example 1, except that the wet sodium-containing bentonite spherical particles were dried at 220° C. for 25 minutes.

[0082] The chemical composition, mineral composition and powder fineness of the modified bentonite powder were the same as those in Example 1.

[0083] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 9.4%; bulk density (g / cm 3 ): 0.92; Deodorization effect (ppm, as NH3): 14.0; Formaldehyde was not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 42; Powdering rate (%): 0.8; Agglomeration strength (times, 30cm drop without breaking): 11.

[0084] Example 9 The sodium-containing bentonite spherical cat litter was prepared in a manner similar to that of Example 1, except that the wet sodium-containing bentonite spherical particles were dried at 290° C. for 25 minutes.

[0085] The chemical composition, mineral composition and powder fineness of the modified bentonite powder were the same as those in Example 1.

[0086] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.3%; bulk density (g / cm 3 ): 0.81; Deodorization effect (ppm, as NH3): 12.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 44; Powdering rate (%): 0.55; Agglomeration strength (times, 30cm drop without breaking): 14.

[0087] Comparative Example Comparative Example 1 The sodium bentonite spherical cat litter was prepared in a similar manner to Example 1, except that 100 kg of natural calcium-based bentonite and 7 kg of sodium carbonate were weighed.

[0088] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 6.7%; bulk density (g / cm 3 ): 0.98; Deodorization effect (ppm, in terms of NH3): 19.1; Water absorption rate (%): 42; Powdering rate (%): 0.90; Agglomeration strength (times, 30cm drop without breaking): 12.

[0089] Comparative Example 2 The sodium bentonite spherical cat litter was prepared in a similar manner to Example 1, except that 100 kg of natural sodium bentonite and 7 kg of sodium carbonate were weighed.

[0090] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 6.8%; bulk density (g / cm 3 ): 0.97; Deodorization effect (ppm, in terms of NH3): 19.2; Water absorption rate (%): 45; Powdering rate (%): 0.89; Agglomeration strength (times, 30cm drop without breaking): 13.

[0091] Comparative Example 3 The sodium bentonite spherical cat litter was prepared in a similar manner to Example 1, except that no sodium carbonate was added.

[0092] The chemical composition of sodium bentonite powder was tested by silicate rock chemical analysis method (GB / T14506.1-14506.28-93). The chemical composition of sodium bentonite powder was as follows: SiO2 54.56%, Al2O3 16.33%, TiO2 0.40%, 5.40%, MgO 4.71%, CaO 2.43%, K2O 0.10%, and the loss on ignition is 15.71%.

[0093] The mineral composition and fineness of the bentonite powder were the same as those in Example 1.

[0094] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.7%; bulk density (g / cm 3): 0.88; Deodorization effect (ppm, in terms of NH3): 16.0; Water absorption rate (%): 41; Powdering rate (%): 0.91; Agglomeration strength (times, 30cm drop without breaking): 10.

[0095] Comparative Example 4 The preparation of sodium bentonite spherical cat litter was carried out in a manner similar to Example 1, except that the sodium bentonite powder was granulated using an aqueous solution without methylcellulose.

[0096] The chemical composition, mineral composition and powder fineness of the bentonite powder were the same as those in Example 1.

[0097] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 7.4%; bulk density (g / cm 3 ): 0.82; Deodorizing effect (ppm, as NH3): 12.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 45; Powdering rate (%): 1.1; Agglomeration strength (times, 30cm drop without breaking): 10.

[0098] Comparative Example 5 The sodium-containing bentonite spherical cat litter was prepared in a manner similar to that of Example 1, except that the wet sodium-containing bentonite spherical particles were dried at 210° C. for 25 minutes.

[0099] The chemical composition, mineral composition and powder fineness of the bentonite powder were the same as those in Example 1.

[0100] The performance and application indicators of sodium bentonite spherical cat litter were tested according to the T / CAQI 377-2024 test method. The performance and application indicators of sodium bentonite spherical cat litter were measured as follows: moisture mass fraction (%): 9.6%; bulk density (g / cm 3 ): 0.84; Deodorization effect (ppm, as NH3): 12.0; Formaldehyde not detected; Lead (mg / kg): 12.0, Arsenic: 1.5; Water absorption rate (%): 41; Powdering rate (%): 0.92; Agglomeration strength (times, 30cm drop without breaking): 10.

[0101] It can be seen from the test results of Examples 1-9 above that by using natural bentonite and adopting the preparation method of the present invention, spherical sodium bentonite cat litter with performance meeting the requirements of T / CAQI 377-2024) can be prepared.

[0102] At the same time, by comparing the test results of Examples 1-9 and Comparative Examples 1-5, it can be seen that the performance indicators and application indicators of the spherical cat litter prepared in Comparative Examples 1-5 are worse than those of the spherical cat litter prepared in Examples 1-9, indicating that the performance indicators and application indicators of the spherical cat litter prepared without using natural bentonite or without using the preparation method described in the present invention are poor, indicating that the comprehensive performance of the spherical cat litter described in the present invention is better.

[0103] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A sodium bentonite spherical cat litter, characterized in that: The sodium-containing bentonite spherical cat litter is prepared from natural bentonite ore, a sodium-containing modifier and an aqueous solution containing a viscous substance; The mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100: (3-8): (21-28); The sodium modification agent is selected from one or more of sodium bicarbonate, sodium carbonate and sodium hydroxide.

2. The sodium bentonite spherical cat litter according to claim 1, characterized in that The mass ratio of the natural bentonite ore, the sodium modifier and the aqueous solution containing the viscous substance is 100:7:

26.

3. The sodium bentonite spherical cat litter according to claim 1, characterized in that The mass concentration of the viscous substance in the aqueous solution containing the viscous substance is 0.3% to 9%.

4. The sodium bentonite spherical cat litter according to claim 1, characterized in that The viscous substance is selected from one or more of polyacrylamide, carrageenan and methyl cellulose.

5. The sodium bentonite spherical cat litter according to claim 1, characterized in that The moisture content of the sodium bentonite spherical cat litter is 6.5%-9.5%, and the bulk density is 0.78-1.02g / cm 3 , deodorization effect ≤19.5ppm, calculated as NH3, formaldehyde not detected, lead ≤30.0mg / kg, arsenic ≤12.0mg / kg; The application indexes of the sodium bentonite spherical cat litter are: water absorption rate ≥42%, pulverization rate ≤0.9%, and agglomeration strength ≥11 times.

6. A method for preparing the sodium bentonite spherical cat litter according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step 1, mixing natural bentonite ore and a sodium modifier evenly, and then extruding, stacking, drying, and grinding to obtain sodium bentonite powder; Step 2: Mix the sodium bentonite powder and the aqueous solution containing the sticky substance to form granules, sieve to obtain wet sodium bentonite spherical particles, and then dry and sieve to obtain sodium bentonite spherical cat litter.

7. The method according to claim 6, characterized in that In step 1, The stacking is carried out at room temperature for 40 to 50 hours.

8. The method according to claim 6, characterized in that In step 1, The drying is carried out at 100-120° C. for 20-45 minutes; The powders ground to a fineness of 200 mesh and below account for more than 92%.

9. The method according to claim 6, characterized in that In step 2, Sieve to obtain 1-4 mm wet sodium bentonite spherical particles; After sieving, the wet sodium bentonite spherical particles are dried at 220-290°C for 20-45 minutes; After drying, fine particles with a particle size of less than 1 mm are removed by sieving, and finally sodium bentonite spherical cat litter with a particle size of 1 to 4 mm is obtained.

Citation Information

Patent Citations

  • Bentonite / modified zeolite compound super absorbent cat litter

    CN103348924A

  • Modified bentonite cat litter and preparation method thereof

    CN104489424A

  • Protein-soil composite multifunctional odor-absorbing cat litter and its preparation method

    CN107711533B

  • Attapulgite natural mineral cat litter

    CN108849559A

  • A multifunctional graphene-bentonite cat litter and its preparation method

    CN109089905B

Cited By

  • Bentonite broken sand for pets and preparation method of bentonite broken sand

    CN121040392A